Service quality and visitor experience as antecedents of revisit intention: the mediating role of place attachment - Indri Ferdiani Suarna; Vanessa Gaffar; Lili Adi Wibowo; Puspo Dewi Dirgantara; Ahmad Azam Sulaiman (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2025)
This study aims to examine the causal relationships among service quality, visitor experience, place attachment, and revisit intention in the context of toll road rest areas in Indonesia. It addresses a growing concern regarding the underutilization and inconsistent visitor loyalty in rest area facilities, particularly in light of Indonesia's expanding toll infrastructure. Grounded in the Theory of Planned Behavior and supported by concepts of emotional place attachment, this research investigates how functional and affective drivers influence users’ behavioral intentions. A quantitative survey was conducted using a purposive sampling method, targeting 210 respondents who had visited Rest Area KM 166A or KM 164B on the Cikopo–Palimanan Toll Road. Data were analyzed using Structural Equation Modeling (SEM) with AMOS 26. Constructs were measured with a five-point Likert scale, and validity was assessed through Confirmatory Factor Analysis (CFA), with all constructs exceeding acceptable CR (>0.98) and AVE (>0.93)thresholds. The results show that service quality significantly predicts both place attachment (β = 0.526, p < 0.001) and revisit intention (β = 0.491, p < 0.001), while visitor experience only influences revisit intention indirectly through place attachment. Mediation analysis confirmed the significant role of place attachment (Sobel test: t = 3.64, p < 0.001). Practically, these findings suggest that improving service delivery and fostering emotional connection through contextual and cultural design can enhance visitor loyalty. Theoretically, the study contributes by clarifying contradictory results in previous tourism literature regarding the direct effect of experience on behavioral intention. However, the study is limited to two rest areas and uses cross-sectional data, limiting the generalizability of the findings. Future research should include comparative or longitudinal designs.